Time to Change for Mental Health and Well-being via Virtual Professional Coaching: Longitudinal Observational Study - Alexis M Jeannotte; Derek M Hutchinson; Gabriella R Kellerman (JMIR Publications, 2021)
BackgroundOptimal mental health yields many benefits and reduced costs to employees and organizations; however, the workplace introduces challenges to building and maintaining mental health that affect well-being. Although many organizations have introduced programming to aid employee mental health and well-being, the uptake and effectiveness of these efforts vary. One barrier to developing more effective interventions is a lack of understanding about how to improve well-being over time. This study examined not only whether employer-provided coaching is an effective strategy to improve mental health and well-being in employees but also how this intervention changes well-being in stages over time. ObjectiveThe goal of this study was to determine whether BetterUp, a longitudinal one-on-one virtual coaching intervention, improves components of mental health and psychological well-being, and whether the magnitude of changes vary in stages over time. This is the first research study to evaluate the effectiveness of professional coaching through three repeated assessments, moving beyond a pre-post intervention design. The outcomes of this study will enable coaches and employers to design more targeted interventions by outlining when to expect maximal growth in specific outcomes throughout the coaching engagement. MethodsThree identical assessments were completed by 391 users of BetterUp: prior to the start of coaching, after approximately 3-4 months of coaching, and again after 6-7 months of coaching. Three scales were used to evaluate psychological and behavioral dimensions that support management of mental health: stress management, resilience, and life satisfaction. Six additional scales were used to assess psychological well-being: emotional regulation, prospection ability, finding purpose and meaning, self-awareness, self-efficacy, and social connection. ResultsUsing mixed-effects modeling, varying rates of change were observed in several dimensions of mental health and psychological well-being. Initial rapid improvements in the first half of the intervention, followed by slower growth in the second half of the intervention were found for prospection ability, self-awareness, self-efficacy, social connection, emotional regulation, and a reduction in stress (range of unstandardized β values for each assessment: .10-.19). Life satisfaction improved continuously throughout the full intervention period (β=.13). Finding purpose in meaning at work and building resilience both grew continuously throughout the coaching intervention, but larger gains were experienced in the second half of the intervention (β=.08-.18), requiring the full length of the intervention to realize maximal growth. ConclusionsThe results demonstrate the effectiveness of BetterUp virtual one-on-one coaching to improve psychological well-being, while mitigating threats to mental health such as excessive and prolonged stress, low resilience, and poor satisfaction with life. The improvements across the collection of outcomes were time-dependent, and provide important insights to users and practitioners about how and when to expect maximal improvements in a range of interrelated personal and professional outcomes.